Gender differences on determinants of good knowledge on recognition of stroke symptoms and actions during a stroke among hypertensive patient - Ching, Siew Mooi *; Chia, Yook Chin *; Devaraj, Navin Kumar; Lim, Hooi Min; Beh, Hooi Chin (Lippincott, Williams & Wilkins, 2023)
Early recognition and action during a stroke are extremely important to improve stroke prognosis. This study aimed to examine the gender difference in the KAP of stroke in hypertensive patients.